Adsorption of Cr(VI) from aqueous solution by adsorbent prepared from paper mill sludge: Kinetics and thermodynamics studies - Gorzin, Fatemeh; Bahri Rasht Abadi, MM (Adsorption science & technology, 2018)
In the present work, a new low-cost activated carbon was prepared from paper mill sludge in order to remove Cr(VI) ions from aqueous solution. The effects of adsorbent dosage, pH, contact time, metal ion concentrations, and temperature on adsorption efficiency were studied by experimental tests. The maximum equilibrium uptake of Cr(VI) by the adsorbent was 23.18 mg g−1 at optimum pH = 4.0, contact time of 180 min, and temperature of 45℃. Analysis of equilibrium adsorption data in terms of several isotherm models revealed that Langmuir isotherm with respect to Freundlich isotherm indicates better agreement with the experimental data. The kinetics of Cr(VI) adsorption onto activated carbon was described with the pseudo-second-order model which indicates the dominance of chemisorption mechanism. Thermodynamic parameters indicated that the Cr(VI) adsorption onto adsorbent was feasible in nature, spontaneous, and endothermic.